Legal Authority and Marital Identity: A Study on the Kalosara Tradition of the Tolaki People in Southeast Sulawesi - Ahmadi; Zainuddin, Asriadi; Zainal, Asrianto; Darlis, Syamsul (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2024)
For the Tolaki indigenous people, a marriage is considered valid when it is conducted in accordance with the kalosara tradition. This signifies that the legitimacy of marriage among the Tolaki people of Southeast Sulawesi is not determined by adherence to Islamic law or state regulations, but by the observance of the kalosara customary practice. This study seeks to explore the kalosara tradition as the prevailing authority in the marriage law of the Tolaki community in Southeast Sulawesi, and to analyze the perspectives of Islamic law through the concepts of ‘urf and maṣlaḥa mursala in relation to this tradition. Employing a qualitative research method with an empirical-normative approach, data were gathered through interviews with traditional leaders, community figures, and religious authorities. The findings of the study indicate that the kalosara tradition in Tolaki community wedding ceremonies consists of three stages: seeking permission, the proposal, and the marriage contract. The Tolaki people regard a marriage as valid only if it adheres to the kalosara tradition, establishing customary law as the dominant form of marriage law within the community. From the perspective of ‘urf, the kalosara tradition is deemed acceptable, as it fulfills the criteria of al-‘urf al-ṣaḥīḥ (good custom). Moreover, the kalosara tradition contributes to social welfare within the Tolaki community of Southeast Sulawesi. This research is expected to make a significant global contribution to the development of studies on marriage law and tradition. Furthermore, it is deserving of recognition as a valuable academic resource addressing societal legal needs concerning the practice of marriage traditions.